Financial Literacy and Financial Planning Factors on Financial Behavior in MSME Actors Providing Agricultural Production Facilities - Khairunnisa, Firstia Nurlaili; Yuliarti, Norita Citra; Suharsono, Riyanto Setiawan (Pubmedia Social Sciences and Humanities, 2024)
For the smooth production of agricultural products, seeds, fertilizers and pesticides are needed. Given this need, SMEs that provide agricultural production facilities are the most important and most needed SMEs as providers of seeds, fertilizers and pesticides. The type of data in this study is quantitative data. The population in this study are SMEs who provide agricultural production facilities with a total of 30 SMEs. Data processing uses IBM SPSS. Financial Literacy for MSME Actors Providing Agricultural Production Facilities has a significant impact on Financial Behavior (Financial Behavior) Financial Planning (Financial Planning) for MSME actors providing Agricultural Production Facilities does not has a significant impact on Financial Behavior (Financial Behavior) MSME actors providing agricultural production facilities have good financial literacy because they have an understanding of finance. Not all of the MSME actors providing agricultural production facilities implement good financial planning, many of them have not thought about short-term and long-term investments, such as obtaining maximum profits and trying to open branches in other areas.